2015
DOI: 10.1017/jfm.2015.310
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing on thin air: how squeeze forces in the air film during non-wetting droplet bouncing lead to momentum transfer and dissipation

Abstract: Millimetre-sized droplets are able to bounce multiple times on flat solid substrates irrespective of their wettability, provided that a micrometre-thick air layer is sustained below the droplet, limiting We to 4. We study the energy conversion during a bounce series by analysing the droplet motion and its shape (decomposed into eigenmodes). Internal modes are excited during the bounce, yet the viscous dissipation associated with the in-flight oscillations accounts for less than 20 % of the total energy loss. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
2
33
1
Order By: Relevance
“…As far as incompressibility is concerned, for standard atmospheric conditions such as those used in recent experiments, excess pressure in the gas cushion is quite low, and the entire evolution process can be safely assumed to be governed by incompressible fluid dynamics as shown by de Ruiter et al. (2015 b ). To justify the incompressibility assumption, we follow the work of Mandre et al.…”
Section: Numerical Set-upmentioning
confidence: 99%
“…As far as incompressibility is concerned, for standard atmospheric conditions such as those used in recent experiments, excess pressure in the gas cushion is quite low, and the entire evolution process can be safely assumed to be governed by incompressible fluid dynamics as shown by de Ruiter et al. (2015 b ). To justify the incompressibility assumption, we follow the work of Mandre et al.…”
Section: Numerical Set-upmentioning
confidence: 99%
“…The related terrestrial problem of contact time τ for a bouncing droplet impacting a hydrophobic surface is studied by Richard et al (2002) and de Ruiter et al (2015), and numerous others. The drop jump time of the present study is quite similar to the drop recoil and rebound phase in such investigations.…”
Section: Drop Jump Time Scale T Jmentioning
confidence: 99%
“…A wide variety of drop-in-air demonstrations are highlighted by Weislogel (2012) and Wollman et al (2016). The drop ejection process is related to the second half of droplet rebound and bounce phenomena from super-hydrophobic surfaces (see Richard et al (2002) and de Ruiter et al (2015), and references contained therein) and the drop jump phenomena observed when drops coalesce on hydrophobic surfaces (Farhangi et al, 2012). The inverse problem of bubbles jumping "downward" from flat surfaces in drop tower experiments is also discussed by Wollman et al (2016) with related work pursued by Suñol and González-Cinca (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal non-coalescence phenomena between a droplet and a wall or a liquid surface can occur under various conditions. Examples include droplet levitation over moving solid walls (Neitzel et al 2001;Smith & Neitzel 2006;Lhuissier et al 2013;Saito & Tagawa 2015;Gauthier et al 2016), atomically smooth horizontal walls (de Ruiter et al 2015), inclined walls (Hodges, Jensen & Rallison 2004;Gilet & 262 E. Sawaguchi, A. Matsuda, K. Hama, M. Saito and Y. Tagawa 1 mm U FIGURE 1. Side view of a levitating droplet over a moving wall.…”
Section: Introductionmentioning
confidence: 99%